KMT5A-methylated SNIP1 promotes triple-negative breast cancer metastasis by activating YAP signaling - Bo Yu; Jun Su; Qiqi Shi; Qing Liu; Jun Ma; Guoqing Ru; Lei Zhang; Jian Zhang; Xichun Hu; Jianming Tang (Nature Communications, 2022)
SNIP1 methylation initiates its oncogenic functions. Here, the authors show that SNIP1 is methylated by KMT5A and this leads to downstream signalling that activates the YAP pathway, resulting in tumorigenesis and metastasis.